2021
DOI: 10.1136/bmjgast-2020-000571
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenterological and hepatic manifestations of patients with COVID-19, prevalence, mortality by country, and intensive care admission rate: systematic review and meta-analysis

Abstract: Background and aimsPatients infected with the SARS-CoV-2 usually report fever and respiratory symptoms. However, multiple gastrointestinal (GI) manifestations such as diarrhoea and abdominal pain have been described. The aim of this study was to evaluate the prevalence of GI symptoms, elevated liver enzymes and mortality of patients with COVID-19.MethodsA systematic review and meta-analysis of published studies that included a cohort of patients infected with SARS-CoV-2 were performed from 1 December 2019 to 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 131 publications
2
55
4
1
Order By: Relevance
“…The development of in-hospital complications was observed more commonly in those who died, with the most significant being AKI, cardiac arrest with ROSC, coagulopathy, and septic shock. These predominated amongst the deceased group as opposed to those discharged and were similarly witnessed in multiple studies [33,34].…”
Section: Discussionmentioning
confidence: 74%
“…The development of in-hospital complications was observed more commonly in those who died, with the most significant being AKI, cardiac arrest with ROSC, coagulopathy, and septic shock. These predominated amongst the deceased group as opposed to those discharged and were similarly witnessed in multiple studies [33,34].…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, a recent study showed that GI manifestations of COVID-19 are also common in patients with inflammatory bowel disease (IBD). 6 However, current data shows patients with IBD were not at higher risk for COVID-19 infection. 7 Patients with IBD are often requiring long-term maintenance medical therapy.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 69%
“…After adjusting for confounding factors, the presence of GI symptoms was still an independent predictor of the composite endpoint, but not death, which indicated that the influence of GI symptoms on the outcomes may not be as strong as the severity of COVID-19. Two previous meta-analyses found that GI symptoms were not associated with death, but they did not include GI bleeding as one type of GI symptoms ( 25 , 26 ). Our study further evaluated whether various types of GI symptoms were associated with the composite endpoint and death, and found that GI bleeding was an independent predictor of the composite endpoint and death.…”
Section: Discussionmentioning
confidence: 99%